Pesantren and the Appreciation of Religious Moderation - Sufyan Syafi'i (INC- Islam Nusantara Center, 2022)
The Pesantren continues to be highlighted as an Indonesian Islamic religious institution. It is highlighted as both an example for education and the harmful issues that are frequently directed towards it. Pesantren Islamic boarding schools are challenged to continue operating in the rapidly changing times. Not only the change in flexibility of teaching methods, but existing values also need to have their meaning enhanced. Religious moderation that offers the concept of value at various points can help to strengthen the pesantren's sense of identity. Through implementation theory-based evaluation, this study tries to measure how well this form of implementation can address and resolve current issues. This paper also aims to offer some reflections on which points can be used as references in formulating policies to promote the value of religious moderation, particularly in the administrative area and impulsivity. In term of quantitative, there have been many forms of study that have discussed the implementation of religious moderation, however, it is rare to find a form of reflection writing that can serve as a space for respite to map the growing problems in the field. This dialogical paper makes use of a qualitative descriptive-analytic database. Abstrak Pesantren terus dinilai sebagai lembaga keagamaan Islam Indonesia. Hal ini sebagai contoh untuk pendidikan dan isu-isu miring sering diarahkan padanya. Pesantren ditantang untuk tetap berjalan di zaman yang berubah dengan cepat. Tidak hanya perubahan metode pengajaran yang fleksibel, tetapi nilai-nilai yang ada juga perlu ditingkatkan maknanya. Moderasi beragama yang menawarkan konsep nilai di berbagai titik dapat membantu memperkuat rasa identitas pesantren. Melalui evaluasi berbasis teori implementasi, penelitian ini mencoba mengukur seberapa baik bentuk implementasi ini dapat mengatasi dan menyelesaikan masalah saat ini. Tulisan ini juga bertujuan untuk menawarkan beberapa refleksi yang poin-poinnya dapat dijadikan acuan dalam merumuskan kebijakan untuk mengedepankan nilai moderasi beragama, khususnya di wilayah administrasi dan impulsif. Dari segi kuantitatif, sudah banyak bentuk kajian yang membahas pelaksanaan moderasi beragama, namun jarang ditemukan bentuk penulisan refleksi yang dapat menjadi ruang jeda untuk memetakan permasalahan yang berkembang di lapangan. Makalah dialogis ini menggunakan basis data deskriptif-analitik kualitatif.